RBM45: Molecular, Cellular, and Evolutionary Biology - Jeffrey, O. Henderson (Journal of DNA And RNA Research, 2024)
This article surveys RBM45 from molecular function and RNA binding to cellular roles and evolutionary conservation. It summarizes emerging links to neurobiology and disease, and highlights tools and models to probe RBM45 biology.
Keywords: RBM45; RNA-binding proteins; exon-intron structure; RNA-binding domain; NLS; NES; HOA domain; frontotemporal lobar degeneration; amyotrophic lateral sclerosis; Alzheimer’s disease